Antibiotics Sensitivity of Bacteria Types Isolated from burns and Wounds in Babylon Governorate - Kbah, Ameer Qusay Abbas (American Journal of Bioscience and Clinical Integrity, 2026)
The current study involved collecting 100 clinical samples, taken directly from burn and wound swabs, from patients of various ages and sexes, between the beginning of November 2025 and the end of December 2025, from both inpatients and outpatients at Al-Hilla Teaching Hospital. The samples were cultured on blood agar and MacConkey agar. Bacterial isolates were identified using selective and differential media. Biochemical tests were then performed to confirm the diagnosis of each isolate. Based on the results of biochemical diagnosis, the bacterial species were Gram-positive: 22 isolates of Staphylococcus aureus, and Gram-negative, comprising 4 bacterial species: 26 isolates of Klebsiella pneumoniae, 14 isolates of Pseudomonas aeruginosa, 12 isolates of Proteus mirabilis, and 8 isolates of Escherichia coli. The antibiotic susceptibility of all different bacterial isolates was tested against 24 different antibiotics using the disc diffusion method. The results showed that many bacterial isolates exhibited multidrug resistance (MDR). The current study indicated that a total of 22 Staphylococcus aureus isolates showed multidrug resistance to the following antibiotics: the highest resistance rate was against ofloxacin and clarithromycin (73%), while clindamycin resistance was 55%. Resistance to doxycycline and chloramphenicol was 27%, while all isolates showed 100% sensitivity to gentamicin. The study also showed that the 26 Klebsiella pneumoniae isolates exhibited varying levels of resistance, including a high resistance rate of 100% to amoxicillin, and resistance rates of 92% to cefotaxime and cefepime. 85% of isolates showed resistance to Ciprofloxacin (31%), Tetracycline (38%), Aztreonam (54%), Amoxicillin-clavulanate (23%), Co-trimazole (15%), Levofloxacin (15%), Gentamicin (23%), Amikacin (8%), Imipenem (8%), and Levofloxacin (15%). Fourteen Pseudomonas aeruginosa isolates showed high resistance to the antibiotics Cefepime (100%), Ceftazidime (86%), and Ticarcillin-clavulanate (71%). Bacterial isolates also showed resistance to Ciprofloxacin, Ofloxacin, and Aztreonam (57%). All isolates showed sensitivity to these antibiotics. With a resistance rate of 100% to Piperacillin/Tazobactam, while Meropenem, Imipenem, and Netilmicin showed low resistance (14%). As for Proteus mirabilis, its isolates showed high resistance (100%) to Amoxicillin, while the resistance rate was 50% for Cefepime, Amoxicillin-clavulanate, and Tetracycline. It also showed high resistance (67%) to Cefotaxime, Gentamicin, Ciprofloxacin, Aztreonam, and Amikacin (33%). Eight E. coli isolates showed 100% resistance to Amoxicillin-clavulanate, Cefepime, Cefotaxime, Amoxicillin, and Ciprofloxacin. Aztreonam, Levofloxacin, Gentamicin 75% and 50%, while the percentage was 25%. In Hassan, there was a high sensitivity (100%) to Tetracycline and Co-triazole.